Rice crop yield and its effect with copper chelate and ozonated water - Llerena-Hidalgo, Ángel; Aguirre Chaw, Cristóbal (Revista Mexicana de Ciencias Agrícolas, 2024)
The golden apple snail (Pomacea canaliculata) (Lamarck) is the pest that has caused the most problems in recent years in rice crops. This pest has significantly reduced the productivity of rice worldwide. The present work was carried out on the Salitre-Baba highway, at km 38 in the province of Guayas, Ecuador 2020. It was an experimental trial at the field level, where different doses were applied (one liter of copper chelate + ozonated water/hectare) and (two liters of copper chelate + ozonated water/hectare). For this, a randomized complete block design (RCBD) and 4 treatments, 1 control, and 4 repetitions were used. Once the rice was harvested, statistical data related to yield were collected. The results show that the yield is not affected by the application of copper chelate and ozone and although there was no significant difference between all treatments, it was observed that the best treatment was T4, which corresponds to the dose of 2 L ha-1 of copper chelate mixed with ozonated water with 2 ppm concentration, where the yield was 3 827.5 ±877.8 kg ha-1, higher compared to T5 (control), which reflected a yield of 1 488.7 ±596.4 kg ha-1 significantly lower due to the presence and effects of the snail. It was concluded that copper chelate with ozonated water can control the golden apple snail in rice crops, and an increase in grain yield was observed.
Keywords: Cooper chelate; Ozone water; Agroecology; Pomacea canaliculata